The effect of exclusive breastfeeding on the probability of infant mortality in the Philippines - Go, Kiara Giselle P. (School of Economics, University of the Philippines Diliman, 2019)
This study examines the effect of exclusive breastfeeding on the probability of infant mortality in the Philippines. Breastfeeding, in general, has shown positive impacts on lowering infant mortality. For this particular study, the researchers aim to focus on exclusive breastfeeding which takes into account non_intake of substitutes to determine whether it will result to a much more significant impact on infant mortality. Infant mortality in less developed countries has been a very important factor to analyze. In the Philippines, though there has been a decreasing trend of infant mortality, it is still quite high relative to those with more advanced economies. The results of our study show that exclusive breastfeeding is indeed statistically significant in lowering the probability of infant mortality in the Philippines, even after controlling variables such as the birth history of infants and some socio_economic factors. In comparison to infants who were not exclusively breastfed, the probability of infant mortality for those who were exclusively breastfed for at least 3 months, 6 months, and 9 months will be lower by 1.64, 1.52, and 1.41 percent respectively. Similarly, exclusively breastfed infants have lower child mortality than those who were not exclusively breastfed_ 1.57, 1.45 and 1.32 percent lower for infants who were exclusively breastfed for at least 3 months, 6 months and 9 months. Other variables that were found to be significant are birth weight and the type of birth delivery. One weakness of this study is that the link between diseases and infant mortality was not included in our regression due to the limitations of our data. Therefore the effect of exclusive breastfeeding on infant mortality may be overstated or understated. We highly recommend a further study on this matter.